Indivíduos em busca de excitação e prazer: análise sociológica de expansão das atividades físicas de aventura na natureza - Contorani, José Roberto Herrera (2006)
The following research has as the main goal the comprehension of development of physical adventure in nature. The way adopted to achieve this goal, goes though the exploration on the transformation in the social habits and the consequences that such transformation cause the modern life. The civilization process, the modernization and the necessities unchained for such events here are opened with the intention of verifying its relation with the activities of leisure. This purpose is marked out with the fact that some activities of leisure, on all mimetic, had been, indeed, transformed by a blind process, that was not thought, not directed, not planned, developed social-historically, as well as the own development of civilization process in a way of reaching the satisfaction throughout these necessities. The goal of this study is to show that these necessities are related to the search for a balance due to the uncomfortable found by the man in its place of living and respective positioning in the civilization evolution. In modern times, the sociability, many times, is based on running days, agitated, stressful and also routine. In this context, some activities of leisure end up presenting better conditions for the satisfaction and balance to these discomforts than others. Based on this context, front to the marketing development reached recently, the physical activities of adventure in the nature are hare studied with the purpose of verifying its condition of restorative of the balance front the necessities generated by the civilization process and the condition of life in a widely urban context.